OSCILLATION CRITERIA FOR LINEAR DIFFERENCE EQUATIONS WITH SEVERAL VARIABLE DELAYS - Benekas, Vasileios; Garab, Ábel; Kashkynbayev, Ardak; Stavroulakis, Ioannis P. (AGH University of Science and Technology Press, 2021)
Abstract. We obtain new sufficient criteria for the oscillation of all solutions of linear delay difference equations with several (variable) finite delays. Our results relax numerous well-known limes inferior-type oscillation criteria from the literature by letting the limes inferior be replaced by the limes superior under some additional assumptions related to slow variation. On the other hand, our findings generalize an oscillation criterion recently given for the case of a constant, single delay. Keywords: oscillation, difference equations, several delays, non-monotone argument, slowly varying function.
Keywords: oscillation; difference equations; several delays; non-monotone argument; slowly varying function; Type of access: Open Access